2006
DOI: 10.1037/0090-5550.51.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse assessment and treatment: The current training and practice of APA Division 22 members.

Abstract: To determine the preparedness of rehabilitation psychologists to work with people with disabilities with primary or secondary substance-related problems by examining their education, training, and current practice. Design: Mail survey. Participants: 76 (47 men, 29 women) Division 22 members of the American Psychological Association. Results: Although 79% of respondents reported treating individuals with alcohol and other drug issues, over half rated their training in substance abuse treatment as inadequate. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Indeed, the majority of social workers, mental health counselors, and psychologists receive no training in substance use or its treatment (Dimoff, Sayette, & Norcross, 2017;Madson, Bethea, Daniel, & Necaise, 2008;Wilkey, Lundgren, & Amodeo, 2013). As a result, most mental health providers feel inadequately trained and in fact do lack the competency needed to treat this population (Burrow-Sánchez, Call, Adolphson, & Hawken, 2009;Cardoso, Pruett, Chan, & Tansey, 2006;Madson et al, 2008). The results of a study of clients seeking outpatient services for depression who also reported hazardous drinking or drug use underscored the low frequency with which mental health providers intervene with substance use (Satre, Leibowitz, Mertens, & Weisner, 2014).…”
Section: Impact Of Provider Training On Treatment Seeking and Engagementmentioning
confidence: 99%
“…Indeed, the majority of social workers, mental health counselors, and psychologists receive no training in substance use or its treatment (Dimoff, Sayette, & Norcross, 2017;Madson, Bethea, Daniel, & Necaise, 2008;Wilkey, Lundgren, & Amodeo, 2013). As a result, most mental health providers feel inadequately trained and in fact do lack the competency needed to treat this population (Burrow-Sánchez, Call, Adolphson, & Hawken, 2009;Cardoso, Pruett, Chan, & Tansey, 2006;Madson et al, 2008). The results of a study of clients seeking outpatient services for depression who also reported hazardous drinking or drug use underscored the low frequency with which mental health providers intervene with substance use (Satre, Leibowitz, Mertens, & Weisner, 2014).…”
Section: Impact Of Provider Training On Treatment Seeking and Engagementmentioning
confidence: 99%
“…Currently, substance misuse remains prevalent in the United States, with recent estimates indicating that 25% of people over the age of 18 binge drank in the past month, and 7% binge drank on at least five occasions in the past month (National Institute on Alcohol Abuse and Alcoholism, 2016). While many struggling with substance use do not actively seek out help (Landau et al, 2000; Regier et al, 1993), rates of problematic drinking are high enough that most therapists (more than 80%) have encountered such individuals in clinical practice (Cardoso et al, 2006; Cellucci & Vik, 2001).…”
Section: Substance Use Treatment: History To Presentmentioning
confidence: 99%
“…Once in treatment, however, there are significant barriers impacting the potential for successful treatment. First, training in this area has not improved significantly, with a recent study finding that the majority of recent psychology graduates feel they lack competency in working with this population (Cardoso et al, 2006). Second, and paradoxically, psychologists’ continued perception of substance use disorders as falling outside of traditional mental health services and needing to be served in specialized treatment settings has largely prevented a patient population with particularly acute needs from being treated by mental health professionals with the highest level of training (Cellucci & Vik, 2001).…”
Section: Substance Use Treatment: History To Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees with alcohol and other drug abuse issues also cost their employers about twice as much in medical and workers' compensation claims as their employees without alcohol and other drug abuse issues (National Institute on Drug Abuse, 2006). The prevalence of alcohol and drug abuse among persons with traumatic disabilities (e.g., traumatic brain injuries and spinal cord injuries) and psychiatric disabilities is also a salient issue in rehabilitation (Cardoso, Pruett, Chan, & Tansey, 2006).…”
mentioning
confidence: 99%